Developing a Pedagogical Electricity and Magnetism Online Concept Test for Pre-service Physics Teachers - Iyon Suyana; Raden Giovanni Ariantara; Feri Apryandi (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2026)
Pedagogical content knowledge (PCK) is a crucial competency for prospective physics teachers. This study aims to develop an online test to assess pedagogical electricity and magnetism concepts in higher education. Participants included 33 prospective physics teachers from a public university in Bandung, four university lecturers, and three physics teachers. A sequential mixed-methods approach was employed, following the Exploratory Design: Instrument Development Model. Qualitative data were collected through questionnaires and literature reviews, while quantitative data were obtained from logical validation using the Learning Object Review Instrument 2.0 and empirical validation. Qualitative data were analyzed using source triangulation, then Many Facet Rasch Measurement (MFRM) was applied for quantitative analysis. The results demonstrate that the Pedagogical Electricity and Magnetism Online Concept Test (PEMOCT) is valid, reliable, and exhibits strong instrument characteristics.